Erucic acid exposure during the first year of life—Scenarios with precise food‐based dietary guidelines. Issue 1 (7th November 2021) - Kersting, Mathilde; Kalhoff, Hermann; Honermeier, Bernd; Sinningen, Kathrin; Lücke, Thomas
Abstract: Recently, the European Food Safety Authority (EFSA) issued a tolerable daily intake (TDI) for erucic acid, which is mainly found in rapeseed oil. Infants may be exposed to erucic acid from rapeseed oil indirectly through maternal consumption via breastmilk or the fat component in formula, and directly as a part of complementary feeding (CF). To check the safety of infant nutrition, scenarios for erucic acid exposure were calculated based on the daily food amounts of the German dietary guidelines. Information on erucic acid concentrations in foods was obtained from European studies for breastmilk, from EFSA samples for formula powder, and from a representative analysis of rapeseed oil samples in the German retail market. 6 scenarios were calculated for the early milk feeding phase (4 formula feeding, 2 breastfeeding) and 8 scenarios for the later CF phase (5 CF +formula feeding, 3 CF +breastfeeding). Out of the 14 scenarios, only 3 resulted in exposures that were definitively below the TDI (range 4.4.–6.0 mg/kg bodyweight; BW). Assuming either high consumption or high concentration led to high exceedances (range 7.5–26.2 mg/kg BW), especially in case of the new EU limits for formula or vegetable oils (33.6 and 43.2 mg/kg BW, respectively). In our scenarios, high erucic acid exposures occurred during a particularly sensitive developmental period. To definitively weigh the potential risks from erucic acid in infants against nutritional benefits of the dietary recommendations, reliable, timely data on erucic acid in breast milk and formula are needed, similar to those from rapeseed oil in Germany. Abstract : In infancy, the diet requires both, an especially high nutritional quality and toxicological safety. In view of the recent TDI for erucic acid issued by EFSA, our scenarios show that the nutritionally safe food‐based dietary guidelines for infancy in Germany may no longer be safe with regard to potential exposure to erucic acid that originates mainly from rapeseed oil. In addition to the strong data base on erucic acid in rapeseed oil in Germany, timely data bases for human milk and formula are needed to definitely decide on the toxicological safety of infant nutrition.